Expansion of Hydra actinoporin-like toxin (HALT) gene family: Expression divergence and functional convergence evolved through gene duplication. (December 2019) - Yap, Wei Yuen; Tan, Katrina Joan Shu Xian; Hwang, Jung Shan
Abstract: Hydra actinoporin-like toxin 1 (HALT-1) was previously shown to cause cytolysis and haemolysis in a number of human cells and has similar functional properties to the actinoporins equinatoxin and sticholysin. In addition to HALT-1, five other HALTs (HALTs 2, 3, 4, 6 and 7) were also isolated from Hydra magnipapillata and expressed as recombinant proteins in this study. We demonstrated that recombinant HALTs have cytolytic activity on HeLa cells but each exhibited a different range of toxicity. All six recombinant HALTs bound to sulfatide, while rHALT-1 and rHALT-3 bound to two additional sphingolipids, lysophosphatidic acid and sphingosine-1-phosphate as indicated by the protein-lipid overlay assay. When either tryptophan 133 or tyrosine 129 of HALT-1 was mutated, the mutant protein lost binding to sulfatide, lysophosphatidic acid and sphingosine-1-phosphate. As further verification of HALTs' binding to sulfatide, we performed ELISA for each HALT. To determine the cell-type specific gene expression of seven HALTs in Hydra, we searched for individual HALT expression in the single-cell RNA-seq data set of Single Cell Portal. The results showed that HALT-1, 4 and 7 were expressed in differentiating stenoteles. HALT-1 and HALT-6 were expressed in the female germline during oogenesis. HALT-2 was strongly expressed in the gland and mucous cells in the endoderm. Information on HALT-3 and HALT-5 could not be found in the single-cell data set. Our findings show that subfunctionalisation of gene expression following duplication enabled HALTs to become specialized in various cell types of the interstitial cell lineage. Highlights: All expressed HALTs were cytolytic towards HeLa cells. Sulfatide is a common lipid-binding site for all HALTs. Subfunctionalisation of actinoporins following gene duplication enabled specialisation of HALTs in the interstitial cell lineage.